1999
DOI: 10.2105/ajph.89.7.1097
|View full text |Cite
|
Sign up to set email alerts
|

Name-based reporting of HIV-positive test results as a deterrent to testing.

Abstract: OBJECTIVES: This study evaluated attitudes toward name-based reporting of HIV. METHODS: One hundred thirty high-risk, male repeat testers received information on the public health benefits of name-based reporting and reported their intentions to test. RESULTS: Of the 67 men who were randomly selected and asked their intentions before hearing the benefits, 63% said they would not test if reporting were required. After hearing the benefits, 19% changed their minds (P < .014). Of the 63 men who were asked only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…), whereas the former is used to signify components that comprise the behavior in question. So, for example, getting tested for HIV, as a behavioral domain, is a behavior that has several attributes, some of which may include concerns about confidentiality (Delerga, Lovejoy, & Winstead, 1998;Woods et al, 1999), perceived stigma (Aggleton & Parker, 2002;Capitanio & Herek, 1999), and so forth. Each behavioral domain can be broken down into meaningful attributes.…”
Section: Focus On Behavioral Attributesmentioning
confidence: 99%
“…), whereas the former is used to signify components that comprise the behavior in question. So, for example, getting tested for HIV, as a behavioral domain, is a behavior that has several attributes, some of which may include concerns about confidentiality (Delerga, Lovejoy, & Winstead, 1998;Woods et al, 1999), perceived stigma (Aggleton & Parker, 2002;Capitanio & Herek, 1999), and so forth. Each behavioral domain can be broken down into meaningful attributes.…”
Section: Focus On Behavioral Attributesmentioning
confidence: 99%
“…4 For example, one study reported that over half of men who had not been tested for HIV cited fear of negative social consequences as an important reason for not getting tested and over 40% of high risk men in another study indicated that name-based reporting of HIV test results would lead them to defer testing. 5,6 HIV-related stigma and discrimination have also been identified as barriers to seeking appropriate healthcare for people living with HIV. 7,8 In a study of HIV-positive adolescents, half of participants reported skipping medication doses to avoid disclosure of HIV status to friends and family.…”
mentioning
confidence: 99%
“…While the issue of whether or not name-based reporting deters testers has been the subject of much research, the results of this research are mixed [4][5][6][7][8][9][10][11]. It is difficult to draw conclusions from this literature because these studies have found that there exists a general lack of knowledge among consumers of HIV testing about their state's HIV reporting regulations.…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of name-based reporting argue non-name data will: (1) be less accurate and more prone to duplication of cases (2) be less efficient to collect and (3) hamper important ancillary services such as partner notification or referrals to care [3,8]. Proponents of a non-namebased method argue: (1) confidential HIV testing may be avoided due to fears associated with name-based method and (2) name-based reporting may raise doubts or mistrust regarding confidentiality of one's HIV status [9][10][11].…”
Section: Introductionmentioning
confidence: 99%